Heat transfer through building envelope materials and their effect on indoor air temperatures in tropics - Wenny Arminda; Maqbul Kamaruddin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2021)
High thermal mass modern building materials are unsuitable to be used in the tropics due to their thermos-physical properties and the ability in absorbing solar radiation, storing and transferring heat into the building, affecting the high indoor air temperature, hence, reducing thermal comfort. However, due to the high demand for building, utilization of this material is avoidable. This study investigated the heat transfer through building envelope materials and their effect on the indoor air temperature of the building through field measurement using a thermal camera and a handle wind meter. The results found that the ceiling is the part of the building which gained the highest indoor surface temperature which reaches 38.6 °C at the apex point at 2pm but decreased significantly to 30.4 °C at 6 pm. Meanwhile, the inner of the northeast wall gained 33.1 °C at the peak temperature and stayed above 30 °C until 10 pm. The indoor air temperature of this unit housing was 36.3 °C at 2 pm with the temperature difference between outdoor and indoor was 2.5 °C. At night, the indoor air temperature was 3.8 °C higher than the outside temperature.